2006
DOI: 10.1371/journal.pmed.0030237
|View full text |Cite
|
Sign up to set email alerts
|

Human Monoclonal Antibody Combination against SARS Coronavirus: Synergy and Coverage of Escape Mutants

Abstract: BackgroundExperimental animal data show that protection against severe acute respiratory syndrome coronavirus (SARS-CoV) infection with human monoclonal antibodies (mAbs) is feasible. For an effective immune prophylaxis in humans, broad coverage of different strains of SARS-CoV and control of potential neutralization escape variants will be required. Combinations of virus-neutralizing, noncompeting mAbs may have these properties.Methods and FindingsHuman mAb CR3014 has been shown to completely prevent lung pat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

13
699
2
4

Year Published

2007
2007
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 672 publications
(718 citation statements)
references
References 50 publications
13
699
2
4
Order By: Relevance
“…For example, the anti-respiratory syncytial virus mAb palivizumab and the anti-coronavirus mAb CR3014 have an IC 50 of 2 mg/ml (29,30), whereas the reported IC 50 of anti-influenza virus, antihuman CMV, and anti-West Nile virus mAbs range between 55 and 92 ng/ml (31)(32)(33). Therefore, the in vitro potency of 5F10 and 8B10 might be adequate for in vivo protection, which remains to be tested.…”
Section: The Journal Of Immunologymentioning
confidence: 99%
“…For example, the anti-respiratory syncytial virus mAb palivizumab and the anti-coronavirus mAb CR3014 have an IC 50 of 2 mg/ml (29,30), whereas the reported IC 50 of anti-influenza virus, antihuman CMV, and anti-West Nile virus mAbs range between 55 and 92 ng/ml (31)(32)(33). Therefore, the in vitro potency of 5F10 and 8B10 might be adequate for in vivo protection, which remains to be tested.…”
Section: The Journal Of Immunologymentioning
confidence: 99%
“…The ferret also serves as an animal model for several inflammatory human diseases, such as influenza and severe acute respiratory syndrome [2,5,17,30,31]. Despite the importance of the ferret in the field of veterinary and human medicine, there have been few reports analyzing the molecular basis of inflammatory cytokines in this animal.…”
mentioning
confidence: 99%
“…This problem may be overcome by using mixtures of mAbs that target various areas of bio-threat agents. Several studies demonstrated that combination therapy with mAb cocktails could prevent escape variants for many viruses including influenza, coronavirus, and lymphocytic choriomeningitis virus [50][51][52]. Also, a cocktail of functional mAbs could provide more protection and target more microbial strains than a single one.…”
Section: Cocktail Of Mabsmentioning
confidence: 99%